2016
DOI: 10.4103/2152-7806.191081
|View full text |Cite
|
Sign up to set email alerts
|

Transition of a herniated lumbar disc to lumbar discal cyst: A case report

Abstract: Background:Another rare cause of lower back pain with radiculopathy is the discal cyst. It is believed to arise from degeneration of a herniated disc, although many other theories of its origin have been proposed. Here, we report a patient with lower back pain/radiculopathy attributed originally to a herniated lumbar disc, which transformed within 6 months into a discal cyst.Case Description:A 42-year-old male had a magnetic resonance (MR) documented herniated lumbar disc at the L4-5 level. It was managed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There was no guideline suggesting the optimal treatment for HDC in the past. Most of the evidences were in the form of case reports or small series [3,11,12]. Several studies with conservative treatment showed low satisfaction rate with a low rate of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no guideline suggesting the optimal treatment for HDC in the past. Most of the evidences were in the form of case reports or small series [3,11,12]. Several studies with conservative treatment showed low satisfaction rate with a low rate of…”
Section: Discussionmentioning
confidence: 99%
“…(MRI). In the reported cases, the surgical excision of the cyst seemed to be a better option than the conservative treatment [3]. While the traditional open surgery was effective, the major drawbacks were massive soft tissue dissection and excessive destruction of the bony structures.…”
mentioning
confidence: 95%
“…Ganglion cysts can develop from any connective tissue of the spine. They have been associated with interspinous ligament [ 3 - 6 ], ligamentum flavum [ 7 - 14 ], PLL [ 15 - 20 ], and disc [ 21 - 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…Bansil et al [ 21 ] reported on a patient suffering from a herniated lumbar disc, with subsequent transformation into a discal cyst within six months. Kim et al [ 26 ] reported on two cases defining the evolution of spinal discal cysts under percutaneous endoscopy.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation